Implementasi Sistem Informasi Manajemen dan Tantangan Sumber Daya Manusia Dalam Meningkatkan Efektivitas Operasional Kantor - Rafika Lutfiyah; Chairunnisa Salsabila Putri Septriani; Yahra Sal Syabilla; Tengku Darmansah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
. The rapid development of information technology has encouraged organizations, both in the public and private sectors, to undergo digital transformation in order to improve operational effectiveness. One of the strategic steps that is widely implemented is the implementation of a Management Information System (MIS), which aims to integrate work processes, improve efficiency, and support data-driven decision-making. However, in practice, MIS implementation often faces significant challenges related to human resources (HR). Common issues include low digital literacy, resistance to change, and a lack of understanding and readiness to operate technology-based systems. These conditions result in suboptimal utilization of MIS in supporting organizational performance. This journal is designed to identify and analyze these challenges and emphasize the importance of human resources as a key factor organization. This journal is designed to identify and examine these challenges and emphasize the importance of HR as a key factor in the success of MIS implementation. The primary objective of this study is to provide a deeper understanding of the interplay between HR readiness and operational effectiveness in the context of managerial digitalization.